2016
DOI: 10.1002/2016jb013273
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on the explosivity of steam‐driven eruptions: A case study of Solfatara volcano (Campi Flegrei)

Abstract: Steam‐driven eruptions, both phreatic and hydrothermal, expel exclusively fragments of non‐juvenile rocks disintegrated by the expansion of water as liquid or gas phase. As their violence is related to the magnitude of the decompression work that can be performed by fluid expansion, these eruptions may occur with variable degrees of explosivity. In this study we investigate the influence of liquid fraction and rock petrophysical properties on the steam‐driven explosive energy. A series of fine‐grained heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 82 publications
0
31
0
Order By: Relevance
“…1(c)). Since a phreatic eruption does not require direct interaction of magma and water (e.g., Germanovich and Lowell, 1995;Hedenquist and Henley, 1985;Lloyd, 1959;Mastin, 1995;Mayer et al, 2015;Montanaro et al, 2016;Ohba et al, 2007), many phreatic eruptions occur without clear precursory events such as deformation and seismicity associated with magma ascent. However, a physical model of rock fracturing (Germanovich and Lowell, 1995) suggested that geophysical precursors, such as anomalous seismicity, ground deformation, and changes in fumarolic and hot spring output, could be detected before phreatic eruptions .…”
Section: Editorial Responsibility: L Piolimentioning
confidence: 99%
“…1(c)). Since a phreatic eruption does not require direct interaction of magma and water (e.g., Germanovich and Lowell, 1995;Hedenquist and Henley, 1985;Lloyd, 1959;Mastin, 1995;Mayer et al, 2015;Montanaro et al, 2016;Ohba et al, 2007), many phreatic eruptions occur without clear precursory events such as deformation and seismicity associated with magma ascent. However, a physical model of rock fracturing (Germanovich and Lowell, 1995) suggested that geophysical precursors, such as anomalous seismicity, ground deformation, and changes in fumarolic and hot spring output, could be detected before phreatic eruptions .…”
Section: Editorial Responsibility: L Piolimentioning
confidence: 99%
“…Accordingly, the commonly assumed “pseudo‐gas” model for the gas‐particle mixture is oversimplified in most volcanic cases. Rapid decompression experiments on porous volcanic rocks have shed light on the process of magma fragmentation and ejection [e.g., Alidibirov and Dingwell , , ; Kueppers et al ., , ; Alatorre‐Ibargüengoitia et al ., , ; Montanaro et al ., ], while analogue injection experiments investigated several aspects of plume dynamics [ Chojnicki et al ., , ; Jessop et al ., ]. Beyond volcanology, the influence of different working conditions on gas and particle velocity is of interest for an enhanced understanding of general gas dynamics [ Sommerfeld , ; Peña Fernández and Sesterhenn , ] or thermal spraying [ Yin et al ., , and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…Our P ‐ T conditions were selected to represent a minimum condition that would be consistent with the observations of the microeruptions of White Island and bubble‐burst events at the surface of the crater lake [ Jolly et al , ]. For the boiling of water in a fixed volume system such as this, see Montanaro et al []. We note that the difference in μ between 20°C at ambient pressure and 120°C pressurized to 2 bar is −1 order of magnitude.…”
Section: Materials Fundamental Rheology and Methodsmentioning
confidence: 99%
“…The application of heat resulted in gas pressurization above the sample. As the water in the sample reached the boiling curve for water, the pressure increased further until the boiling pressure of 2 bar (Figure 2b) resulting in a negligible volume reduction of water [Montanaro et al, 2016]. Water and clay volume are conserved.…”
Section: 1002/2017gl073641mentioning
confidence: 99%